Development of Sustained Release Matrix Tablets of Metformin Using Natural Gums as Release Retardants - Dushyant Singh,; Vikas Sharma,; Dr. Nasiruddin Ahmad Farooqui,; Naeem, (Asian Journal of Pharmaceutical Research and Development, 2026)
For treatment of DM there are several available drugs treatment for glycemic regulation. So that systematic management for glycemic index still cure completely still challenges for most of medical scientific fraternity. Thus its now became pathological treatment of disease advancement in perspective. In response to this todays life diabetes mellitus II like metformin hydrochloride. However in case of disadvantages fever compliance gastrointestinal side effect due to bio-half-life required more dose for long term treatment. For advancement according to raise efficacy. The current work aims to develop metformin hydrochloride sustained release matrix tablets using natural gums as release retardants in order to improve therapeutic efficacy and patient compliance. Natural gums like gum acacia, xanthan gum, and guar gum will be studied as hydrophilic matrix-forming agents because to their low toxicity, affordability, biodegradability, and biocompatibility. Wet granulation or direct compression will be used to create sustained release matrix tablets using various natural gum concentrations.